2023
DOI: 10.3390/en16062847
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Renewable Energy Efficiency and Renewable Energy in Driving Environmental Sustainability in India: Evidence from the Load Capacity Factor Hypothesis

Abstract: Policymakers and environmental scientists have proposed numerous measures toward achieving a sustainable environment. Some of these measures include the efficient use of energy and a clean energy transition. This study empirically investigates the role of non-renewable energy efficiency and renewable energy utilization in driving environmental sustainability in India over the period from 1965 to 2018. Using the approach of the Dynamic Autoregressive Distributed Lag (DyARDL) simulations, the empirical evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Accordingly, a 1% increase in REC reduces the EFPI by −0.166% (0.1), −0.175% (0.2), −0.185% (0.3), −0.193% (0.4), −0.200% (0.5), −0.208% (0.6), −0.216% (0.7), −0.224% (0.8), and −0.238% (0.9). These findings are consistent with the results of Adebayo [48], Adebayo and Samour [52], Alola et al [53], Destek and Sinha [44], Dogan and Pata [49], Fakher and Inglesi-Lotz [50], Shang et al [51], and Sharif et al [45]. However, these findings contradict the results of the study carried out by Xu et al [54].…”
Section: Empirical Findings and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accordingly, a 1% increase in REC reduces the EFPI by −0.166% (0.1), −0.175% (0.2), −0.185% (0.3), −0.193% (0.4), −0.200% (0.5), −0.208% (0.6), −0.216% (0.7), −0.224% (0.8), and −0.238% (0.9). These findings are consistent with the results of Adebayo [48], Adebayo and Samour [52], Alola et al [53], Destek and Sinha [44], Dogan and Pata [49], Fakher and Inglesi-Lotz [50], Shang et al [51], and Sharif et al [45]. However, these findings contradict the results of the study carried out by Xu et al [54].…”
Section: Empirical Findings and Discussionsupporting
confidence: 87%
“…The empirical outcome indicates that renewable energy consumption plays an active role in improving the environmental quality. Employing the D-ARDL approach, Alola et al [53] found that renewable energy consumption supported environmental sustainability by positively influencing the environmental quality in India during the period 1965-2018.…”
Section: The Studies On the Nexus Between Renewable Energy And Enviro...mentioning
confidence: 99%
“…Environmental degradation is the endogenous variable. By following a study by Alola et al ( 2023a ) we measure environmental degradation with the LCF , which considerably compares the existing biocapacity with ecological footprint. By this measurement, we demonstrate a certain ecological threshold, which means that its increases correspond to a decrease in environmental degradation and vice versa.…”
Section: Data Outline and Model Developmentmentioning
confidence: 99%
“…In addition, the nature and patterns of the impact of renewable energy, FDI , economic expansion, and urbanization on LCF are also examined. While only a few studies have implemented LCF as an environmental indicator for the USA (Pata 2021 ; Pata et al 2023b ; Alola et al 2023a ), the current study expands the literature by accommodating more potential and key indicators with the use of recently developed dynamic simulated autoregressive distributed lag method (DSARDL). Specifically, our study contributes to the literature by applying the LCF which measures both the demand and supply aspects of the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation